Clinical Outcomes of Male Subjects With Moderate COPD Based on Maximum Mid-Expiratory Flow. - Aktan, Ridvan; Ozalevli, Sevgi; Ozgen Alpaydin, Aylin (Respiratory Care, 2021)
BACKGROUND: Although FEV1 and FEV1/FVC are accepted as standard parameters in treatment follow-up, these parameters have a limited ability to predict clinical outcomes in patients with COPD. However, small airways dysfunction, which is determined by maximum mid-expiratory flow, is variable in the same stage of patients with COPD, even if their FEV1 and FEV1/FVC are similar. The aim of this study was to compare pulmonary function, the severity of perceived dyspnea, the severity of fatigue, physical activity level, and health-related quality of life based on the severity of small airways dysfunction in male subjects with moderate COPD. METHODS: The study consisted of 96 subjects with moderate COPD. Pulmonary function tests, the distance achieved on the 6- min walk test, the modified Medical Research Council Dyspnea Scale, the International Physical Activity Questionnaire - short form, the Fatigue Severity Scale, the St George Respiratory Questionnaire, and Short Form 36 questionnaire were evaluated in all subjects. After calculating the mean percent of predicted maximum mid-expiratory flow for the entire sample, subjects were divided into 2 groups: below average (Group 1, n = 54 subjects) and above average (Group 2, n = 42 subjects). RESULTS: There were no differences between the groups in age, body mass index, cigarette consumption, percent of predicted FEV1, and FEV1 /FVC (P = .55, .61, .19, .09, and .15, respectively). Scores from the Fatigue Severity Scale and the modified Medical Research Council dyspnea scale were significantly higher in Group 1 (P = .003 and P = .002, respectively); in addition, results from the 6-min walk test and the International Physical Activity Questionnaire - short form scores were significantly lower (P = .001 and P < .001, respectively). CONCLUSIONS: Increased small airways dysfunction led to increased perception of dyspnea and fatigue, as well as poor exercise capacity and health-related quality of life in male subjects with COPD. We suggest that it may be useful to consider the maximum mid-expiratory flow in addition to FEV1 and FEV1/FVC in the treatment and follow-up of male patients with moderate COPD.